The Relationship between the Level of Knowledge and Attitude with Community Preparedness in Natural Disaster Management - R Arwanpitu Elly, Muhammad Z; A. Metekohy , Febby; Widiyati, Wiwik (Bantayang Omni Cendekia, 2024)
Background: The National Disaster Management Agency (BNPB) states that natural disasters are disasters caused by events or series of events caused by nature, including earthquakes, tsunamis, erupting mountains, floods, droughts, typhoons, and landslides. Objective: The purpose of the study was to determine the relationship between the level of knowledge and attitudes with community preparedness in handling RT 01 natural disasters in Batumerah Village. Methods: This type of research uses a correlational research design, this study looks for relationships between variables. The approach in this study uses a cross sectional approach. Sampling uses purposive sampling or sampling by determining certain criteria. Data Analysis using chi-square test. Results: The results show the results of the value p = 0.01 where the value of p ≤ 0.05 so that Ha is sent, and the attitude with preparedness shows results with a value of p = 0.00 where the value of p ≤ 0.05 so that Ha is accepted. Based on the results of the study, there is a relationship between the level of knowledge and attitudes with preparedness in natural disaster management in RT 01 Batumerah Village. Conclusion: People's attitudes are also influenced by several factors such as personal experience, the influence of others, mass media, and emotional. The attitude of the community is positive because many people are very concerned about the arrival of disasters, and participate in mitigation efforts, and also have rescue equipment